The Paris library : [large type] a novel - Skeslien Charles, Janet (Wheeler Publishing Inc., 2021)
"Paris, 1939. Young, ambitious, and tempestuous, Odile Souchet has it all: Paul, her handsome police officer beau; Margaret, her best friend from England; her adored twin brother Remy; and a dream job at the American Library in Paris, working alongside the library's legendary director, Dorothy Reeder. But when World War II breaks out, Odile stands to lose everything she holds dear - including her beloved library. After the invasion, as the Nazis declare a war on words and darkness falls over the City of Light, Odile and her fellow librarians join the Resistance with the best weapons they have: books. They risk their lives again and again to help their fellow Jewish readers. When the war finally ends, instead of freedom, Odile tastes the bitter sting of unspeakable betrayal. Montana, 1983. Odile's solitary existence in gossipy small-town Montana is unexpectedly interrupted by Lily, her neighbor, a lonely teenager longing for adventure. As Lily uncovers more about Odile's mysterious past, they find they share a love of language, the same longings, the same lethal jealousy. Odile helps Lily navigate the troubled waters of adolescence by always recommending just the right book at the right time, never suspecting that Lily will be the one to help her reckon with her own terrible secret. Based on the true story of the American Library in Paris, The Paris Library explores the geography of resentment, the consequences of terrible choices made, and how extraordinary heroism can be found in the quietest of places."--